Crossbreeding of Ayrshire, Brown Swiss, and Sahiwal cattle for annual and lifetime milk yield in the lowland tropics of Kenya - Thorpe, W.R.; Morris, C.A.; Kang'ethe, P. (Elsevier, 1994)
Records from 1577 cows borm from 1973 to 1983 on a ranch in lowland Kenya were analyzed for age at first calving, lactation length, lactational milk yield, calving interval, annual milk yield, and, for cows born from 1973 to 1979, number of calvings, productive lifetime in the herd, and lifetime milk yield. Partial lifetime yield (<<-4> lactations) was studied for all cows. Rotational crosses of Ayrshire and Sahiwal, the crosses between them (interbreds), and the crosses-sired by Brown Swiss from the rotational crosses were compared. The Ayrshire-sired rotational crosses yielded 4.8 percent more milk during a 19-d longer lactation and with a calving interval that was 14 d longer than those sired by Sahiwal. Milk yield for completed lactations of interbred cows was 4.5 percent less, and milk yield of Brown Swiss crosses was 9.5 percent more, than the rotational crosses. Livetime milk yields were 48 percent greater for the rotational crosses sired by Ayrshire than by Sahiwal. Interbreds yielded 34 percent less than the average of the rotational crosses. Over partial lifetimes, the rotational crosses sired by Ayrshire yielded 45 percent more milk than those sired by Sahiwal; the interbreds and the crosses sired by Brown Swiss yielded 34 percent less and 62 percent more milk, respectively, than the mean of the rotational crosses.